(untitled) (OdontoInvestigación, 2022)
The aim of this study was to evaluate the surface roughness of zirconia-reinforced lithium silicate ceramics treated with three different intraoral polishing systems from the manufacturers Garrison, Ultradent and Jota. The specimens were Celtra Duo ceramics (Dentsply Sirona) modeled by CAD/CAM in a CEREC unit, and then glazed. The glazed specimens were worn out with a diamond bur to simulate an occlusal adjustment in dental restorations and then treated with the different intraoral polishing systems. Polishing procedures were performed at two intervals of 40s each. Data was statistically analyzed using Student T-tests. All three systems managed to significantly reduce the roughness of the milled surface at the end of the first polishing interval, with significant differences between the three systems. In addition, it was observed that, at the end of the second interval, two systems achieved similar surface roughness, but smoother than the third system. None of the systems managed to recover the original roughness of the glazed ceramic surface. Finally, significant differences from one interval to the next suggest that surface roughness can be further reduced by extending polishing time; however, the increase in polishing time can influence the service life of intraoral instruments and working time. Consequently, the time needed to achieve optimal smoothness in each system should be considered as a key performance aspect in future research on intraoral polishing systems.